Simulation of metal filling progress during the casting process - Sulaiman, S.; Hamouda, A.M.S.; Abedin, S.; Osman, M.R. (Elsevier Science S.A.Lausanne, 2000)
Metal filling in pressure die-casting is a complex process where performance is governed by a number of design variables. The filling analysis of non-Newtonian fluid is based on the Navier-Stokes equations. In this paper a complete analysis is accomplished by combining the network element method and fluid flow analysis to describe an incremental flow front movement. It has been demonstrated that the developed two-dimensional numerical scheme for simulating mould filling behaviour can provide reliable results; such as pressure, velocity and temperature variation within the cavity. The temperature and pressure are important to the finished product quality and may be used to optimise the moulding process. The effect of draft angle over metal filling process is also investigated. The results obtained from the analysis have been verified against analytical results and published data.